The role of universities in developing human resource capabilities and skills for educational services - sijad khalf husayn; Solaf Abdel Qader Hamid; Marwa Hashem Hassan Kamal ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
The current research aims to identify the interest of Iraqi universities in developing the academic capabilities and skills of university services, and to present some proposals and recommendations related to developing this role. The descriptive approach was adopted, and a sample of (150) individuals was chosen from the administrative and academic leaderships at Yarmouk University College and the University College of Mesopotamia. The research found that there is a growing interest from private universities in developing the capabilities and skills of university services. This is evident in the interest in considering the entry of universities in international rankings as a goal and an indicator of the quality of higher education in Iraq. By supporting the Ministry's plans to reduce slack, create an academic environment, raise scientific levels, and strive to contract with the state or companies to complete the work. As well as encouraging investment in expanding colleges and raising their academic levels. The research recommended the necessity of seeking to communicate with the community and meet its needs, and the need to provide an administrative guide that helps students and researchers to know the mechanism of university services provided to them, And to review the style and methods of university administration in order to be compatible with the goals of university education and its strategic directions, and to pay attention to research aimed at applying scientific and technological knowledge to improve quality and develop academic capabilities and skills.